5‐hydroxytryptophan attenuates imiquimod‐induced psoriasiform dermatitis probably through inhibition of IL‐17A production and keratinocyte activation - Hsu, Peng‐Yang; Yang, Hui‐Ju; Yang, Tao‐Hsiang; Su, Che‐Chun (Experimental dermatology, 2018)
Psoriasis is a chronic autoimmune disease with keratinocyte activation and lymphocyte infiltration in the skin. Our previous study found that 5‐hydroxytryptophan (5(OH)Trp), a tryptophan metabolite, alleviated collagen‐induced arthritis and suppressed cytokine production. In this study, we evaluated the effects of 5(OH)Trp in a mouse model for psoriasiform dermatitis, induced by imiquimod (IMQ). We showed that 5(OH)Trp significantly reduced the cumulative scores, epidermal thickness and ki‐67 expression in the skin. In addition, 5(OH)Trp decreased local and systemic inflammation. Moreover, 5(OH)Trp significantly inhibited keratinocyte activation with decrease in IL‐6 production and p‐Erk1/2 and p‐STAT3 expression. 5(OH)Trp also inhibited the differentiation of IFN‐γ‐ and IL‐17A‐expressing CD4+ T cells and related cytokine production (TNF‐α, IL‐6, IL‐17A and IFN‐γ) in splenocytes. In conclusion, 5(OH)Trp can inhibit imiquimod‐induced psoriasiform dermatitis in mice and inhibit activation in keratinocytes and splenocytes.